Grey shade of work environment triad – effect of supervisor ostracism and perceived organizational obstruction on employees' behaviour: a moderated-mediation model. Issue 5 (1st June 2020) - Akhtar, Muhammad Waheed; Syed, Fauzia; Javed, Muzhar; Husnain, Mudassir
Abstract : Purpose: This study, based on the moderated-mediation model, investigates the indirect effect of facades of conformity in the relationship between supervisor ostracism and unethical work behaviour. Furthermore, this study tested the moderating role of perceived organizational obstruction in the aforementioned relationship through facades of conformity. Design/methodology/approach: Employing a multi-wave and two-source data from employees and peers ( n = 264) of the services sector in Pakistan, the authors tested the proposed framework using Hayes and Preacher moderated-mediation technique. Findings: The findings reflect that supervisor ostracism encourages unethical behaviour at the workplace. Further, results revealed that facades of conformity mediated this direct relationship. Moreover, the authors found that perceived organizational obstruction moderated the relationship between supervisor ostracism and facades of conformity. Results also confirm that perceived organizational obstruction moderates the mediated relationship. Research limitations/implications: The paper concludes with a discussion, managerial implications, limitations and directions for future research. Originality/value: This study added value in the literature of supervisor ostracism, facades of conformity, unethical work behaviour and perceived organizational obstruction.